Acetate uptake efficiency of polyphosphate-accumulating organisms under exposure to surfactants - Tsuji, K (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
We investigated the influence of surfactants such as linear alkylbenzene sulfonates (LAS) and alcohol ethoxylates (AE) on acetate uptake by polyphosphate-accumulating organisms (PAOs) under anaerobic conditions, using the phosphate requirement for acetate uptake (+DeltaP/-DeltaAc ratio). In order to estimate the +DeltaP/-DeltaAc ratio, anaerobic batch tests were conducted using activated sludge collected from an anaerobic/oxic sequencing batch reactor used to treat municipal wastewater continuously supplemented with a detergent containing LAS and AE. We demonstrated that LAS and AE have both positive and negative impacts on acetate uptake by PAOs. The disadvantage is that long-term exposure to the detergent inhibits acetate uptake by PAOs, thus deteriorating the efficiency, even if the surfactants are no longer present during the tests. Furthermore, the existence of LAS and/or AE with acetate further diminishes the efficiency. The advantage is that LAS and AE are potential sources of polyhydroxyalkanoate for PAOs, because acetate is produced from the surfactants under anaerobic conditions